A new approach for load flow calculation in AC/DC distribution networks considering the control strategies of different converters. (12th May 2016) - Mousavizadeh, Saeed; Haghifam, Mahmoud‐Reza; Shariatkhah, Mohammad‐Hossein
Summary: Utilization of AC/DC distribution networks has become more reasonable because of the recent developments in power electronic devices and increasing employment of DC electronic loads. In this paper, load flow calculation problem in AC/DC distribution networks is addressed. Because a large number of load buses in bothAC andDC parts and high R/X ratios in the AC part of these networks can lead to the divergence of recent Jacobian matrix based methods, in this paper, a new direct approach based on backward forward sweep algorithm is presented. Comprehensive investigation considering weakly meshed and different types of converters and their control strategies is also carried out. The presented algorithm is applied to the test systems equipped with different types of converters. The results demonstrate the validity and capability of the proposed method. Copyright © 2016 John Wiley & Sons, Ltd.